An electrically controllable all-solid-state Au@graphene oxide actuator. Issue 34 (24th March 2016) - Shi, Qiuwei; Hou, Chengyi; Wang, Hongzhi; Zhang, Qinghong; Li, Yaogang
Abstract : A novel electrically controllable Au@GO actuator with excellent actuating performance which possesses electrolyte-free, real time controlled actuation and patterning capabilities. Abstract : A novel all-solid electrically controllable Au@graphene oxide (GO) actuator with a bilayer structure is reported to address many of the limitations of traditional electrical-driven materials including complicated layouts and high electric fields. Specifically, the obtained Au@GO actuator possesses electrolyte-free, real time controlled actuation and patterning capabilities.